2005
DOI: 10.1093/ajcn/82.6.1327
|View full text |Cite
|
Sign up to set email alerts
|

Cow milk is not responsible for most gastrointestinal immune-like syndromes—evidence from a population-based study

Abstract: In an unselected cohort of young adults, 8% reported food-related gastrointestinal symptoms. The finding of immunologic activity implied the existence of a food-related gastrointestinal syndrome but not one induced by CM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 44 publications
0
8
0
Order By: Relevance
“…Even though a former study showed a higher‐than‐expected prevalence of lactase downregulation (14%) among Swedish schoolchildren , others have shown that over‐reporting of lactose intolerance is frequent even in populations in which lactase downregulation is common . These findings suggest that symptoms of lactose intolerance might be caused by underlying mechanisms other than lactase downregulation . Further evaluation of these children including genotype testing and oral challenges would be necessary to differentiate symptoms caused by lactase downregulation from lactose intolerance like symptoms due to other gastrointestinal conditions like irritable bowel disease .…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Even though a former study showed a higher‐than‐expected prevalence of lactase downregulation (14%) among Swedish schoolchildren , others have shown that over‐reporting of lactose intolerance is frequent even in populations in which lactase downregulation is common . These findings suggest that symptoms of lactose intolerance might be caused by underlying mechanisms other than lactase downregulation . Further evaluation of these children including genotype testing and oral challenges would be necessary to differentiate symptoms caused by lactase downregulation from lactose intolerance like symptoms due to other gastrointestinal conditions like irritable bowel disease .…”
Section: Discussionmentioning
confidence: 97%
“…These findings suggest that symptoms of lactose intolerance might be caused by underlying mechanisms other than lactase downregulation (9). Further evaluation of these children including genotype testing and oral challenges would be necessary to differentiate symptoms caused by lactase downregulation from lactose intolerance like symptoms due to other gastrointestinal conditions like irritable bowel disease (7,9,11).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations